Elucidating the Catalytic Power of Glutamate Racemase by Investigating a Series of Covalent Inhibitors. (21st November 2018) - Vance, Nicholas R.; Witkin, Katie R.; Rooney, Patrick W.; Li, Yalan; Pope, Marshall; Spies, M. Ashley
Abstract: The application of covalent inhibitors has experienced a renaissance within drug discovery programs in the last decade. To leverage the superior potency and drug target residence time of covalent inhibitors, there have been extensive efforts to develop highly specific covalent modifications to decrease off‐target liabilities. Herein, we present a series of covalent inhibitors of an antimicrobial drug target, glutamate racemase, discovered through structure‐based virtual screening. A combination of enzyme kinetics, mass spectrometry, and surface‐plasmon resonance experiments details a highly specific 1, 4‐conjugate addition of a small‐molecule inhibitor with a catalytic cysteine of glutamate racemase. Molecular dynamics simulations and quantum mechanics–molecular mechanics geometry optimizations reveal the chemistry of the conjugate addition. Two compounds from this series of inhibitors display antimicrobial potency similar to β‐lactam antibiotics, with significant activity against methicillin‐resistant S .  aureus strains. This study elucidates a detailed chemical rationale for covalent inhibition and provides a platform for the development of antimicrobials with a novel mechanism of action against a target in the cell wall biosynthesis pathway. Abstract : Crippling the cysteine : Through structure‐based virtual screening, we present a series of covalent inhibitors of glutamate racemase, an antimicrobial drug target. Using experimental and computational techniques, we provide a chemical rationale for the conjugate addition of a small‐molecule inhibitor with a catalytic cysteine of glutamate racemase. Additionally, each compound was tested against a panel of opportunistic pathogens to determine their antimicrobial potency.